2003
DOI: 10.1161/01.cir.0000084553.92734.83
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lead aVR in Patients With a First Non–ST-Segment Elevation Acute Myocardial Infarction

Abstract: Background-ST-segment elevation in lead aVR has been associated with severe coronary artery lesions in patients with acute coronary syndromes, but the prognostic significance of this finding is unknown. Methods and Results-We analyzed the initial ECG in 775 consecutive patients admitted to our center with a first acute myocardial infarction without ST-segment elevation in leads other than aVR or V 1 . The rates of in-hospital death in patients without (nϭ525) and with 0.05 to 0.1 mV (nϭ116) or Ն0.1 mV (nϭ134) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
3
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(92 citation statements)
references
References 39 publications
1
86
3
2
Order By: Relevance
“…Similarly other studies mentioned that Coronary artery disease (CAD) affects male more frequently and severely than female. [8][9][10] Regarding the risk factors, it was observed in this series that smoker was 68. About the complications, hypotension 6.7%, cardiogenic shock 6.7% and arrhythmias 6.7% in group I but not found in group II.…”
Section: Methodsmentioning
confidence: 55%
“…Similarly other studies mentioned that Coronary artery disease (CAD) affects male more frequently and severely than female. [8][9][10] Regarding the risk factors, it was observed in this series that smoker was 68. About the complications, hypotension 6.7%, cardiogenic shock 6.7% and arrhythmias 6.7% in group I but not found in group II.…”
Section: Methodsmentioning
confidence: 55%
“…The degree of STE in aVR, though not independent of ST depression, has strong association with outcome independent of clinical factors such as Killip class and blood pressure [74,76]. Barrabes et al [74] studied 775 non-STEMIs and found that, compared to no STE in aVR, STE of 0.5 to 1.0 mm had odds ratio (OR) for death of 4.2 (1.5-12.2), and STE of C1.0 mm had OR of 6.6 (2.5-17.6). There were 475 who underwent angiography; of those with C1 mm of STE in aVR (n = 92), 48 % had three-vessel disease and 18 % had LMCA disease, compared to 21 and 4 % for those with \1 mm STE in aVR [74].…”
Section: Lead Avr In Non-ste-acsmentioning
confidence: 90%
“…More recent claims that ST elevation in aVR is independent of ST depression in these opposing leads have not been substantiated for non-STEMI, though this appears to be true for STEMI (see above). Nevertheless, it is convenient to use one lead with ST elevation (aVR) as a substitute for many others with ST depression, such that, in non-STE-ACS, the degree of ST elevation in aVR correlates with the number of leads with ST depression, the depth of the ST depression, and the sum of ST depressions [67,[73][74][75][76]. In all studies, measurements of the ST segment are at 80 ms after the J-point for ST depression and 20 ms after the J-point for ST elevation, both relative to the TP segment.…”
Section: Lead Avr In Non-ste-acsmentioning
confidence: 99%
“…1 ST elevation in lead aVR in patients with first NSTEMI has been associated with higher in hospital mortality and higher prevalence of left main or three-vessel disease, despite not having higher levels of creatine-kinase MB levels. 46 Lead aVR point ß180 degrees to the midpoints of leads I and II. As lead aVR and leads I, II, and V 5 -V 6 point to opposite direction, ST depression in these leads is almost always accompanied by ST elevation in aVR.…”
Section: The Ecg In Patients With Ongoing Typical Symptomsmentioning
confidence: 99%